The effectiveness of smart card media on mathematics learning interest and achievement in third-grade elementary school students - Okta Prastu Dinda Sari; Budiharti Budiharti (State Islamic University of North Sumatra, 2024)
This research aims to determine the effectiveness of using smart card media in influencing the interest and learning achievement of third-grade students at Muhammadiyah Ambarbinangun Elementary School in the mathematics division. The research method employed is quasi-experimental. The study found that the use of smart card learning media effectively influenced both learning interest and achievement. Hypothesis testing revealed that the mean rank value for the experimental class (33,69) was higher than the control class (19.31), indicating differences in learning interest between the two groups. Similarly, in terms of learning achievement, the t-count value (4.578) exceeded the t-table (2,009), demonstrating a significant difference in learning achievement between the experimental and control classes. Post-test scores further supported this, with the experimental class achieving a higher score (81,15) compared to the control class (65,38). Based on statistical analysis, the significance value for interest in learning was less than 0,05 (0,01 < 0,05), indicating that smart cards were more effective than division table media. Similarly, for learning achievement, the significance value was also less than 0.05 (0.00 < 0.05), reinforcing the superiority of smart card media over division table media.